Innovative Learning Planning in the Pancasila Student Profile Strengthening Project in Islamic Religious Education in Madrasah Ibtidaiyah and Elementary Schools - Azizi, Alfan Nur; Masitoh, Dewi (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2024)
This research aims to examine innovations in lesson planning within the context of the Project to Strengthen the Students Profile of Pancasila in Islamic Education at Madrasah Ibtidaiyah and Elementary Schools. Through a literature review method, the study identifies innovative strategies that can be applied to enhance the Pancasila student profile. The analysis includes educational theories, previous research, and the concept of the Pancasila student profile, along with its relevance to Islamic education at the elementary level. The findings indicate that innovations in lesson planning – such as using educational technology, project-based learning approaches, and integrating Pancasila values into the curriculum – can improve the effectiveness of teaching and learning. These findings have practical implications for educators in designing and implementing innovative teaching strategies to support strengthening the Pancasila student profile.